Optimization of Bank Prudential Principles on MSME Loans in Batam City - Rahmad Setyawan; Triana Dewi Seroja; Hari Sutra Disemadi (Universitas Sebelas Maret, 2025)
The Micro, Small and Medium Enterprises (MSMEs) sector has a significant role in Indonesia's economic development and is considered the main pillar of the national economy. The legal umbrella has been formulated by the government to protect the existence of MSMEs in carrying out their activities such as the distribution of Micro Business Credit (KUM) and People's Business Credit (KUR). However, there are still obstacles such as bad credit or Non-Performing Loan (NPL) which is a challenge in itself, so that the principle of prudence in banking needs to be enforced to manage the risk of bad credit as regulated in Law Number 10 of 1998 concerning Banking and confirmed in Bank Indonesia Regulations in order to maintain banking system stability and realize economic justice. This research uses empirical legal research method where the main focus is to analyze the effectiveness of the implementation of prudential banking principles in the distribution of equitable MSME loans in Batam City. The result of the research shows that there is a high commitment from the banks in Batam City in implementing the prudential principle through thorough and continuous evaluation of the legality, financial capacity, and collateral of prospective debtors, as well as regular monitoring of the development of MSMEs. These measures help maintain the Non-Performing Loan (NPL) ratio and support the sustainability of MSMEs in Batam City.